Towards the optimization of the Cs evaporation configuration for long pulse operation of negative ion sources. Issue 1 (1st April 2022) - Mimo, A.; Wimmer, C.; Wünderlich, D.; Fröschle, M.; Fantz, U.
Abstract: Negative ion sources for neutral beam injection rely on surface production of negative ions on a caesiated low work-function surface (plasma grid). To maintain the low work function in long pulses (one hour) and the desired source performance (extracted H - /D - ions and limited co-extracted electrons), Cs needs to be constantly delivered onto the plasma grid. The CsFlow3D code was applied to the RF driven negative ion source ELISE to simulate the evaporation and the plasma-assisted redistribution of Cs. The Cs flux stability is investigated for consecutive one hour plasma pulses and compared with experiments. The effect of different positions of the Cs oven for the case of ELISE equipped with two racetrack shaped RF drivers was investigated: a considerable increase of the Cs flux occurs when evaporating where the plasma is in contact with surfaces, as confirmed also by the back-tracking of the Cs particles reaching the PG. Additionally, an alternative evaporation method close to the plasma grid was designed with the help of CsFlow3D and tested in BATMAN Upgrade, with the aim of increasing the Cs flux onto the PG and achieve a better control of caesiation in long pulses.